2022
DOI: 10.1002/cphc.202200288
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Assisted Dinitrogen Activation on Small Cobalt Clusters: Co4N9+ with Enhanced Stability

Abstract: We have performed a study on the accommodation of nitrogen doping toward superatomic states of transition metal clusters. By reacting cobalt clusters with N2 in the presence of plasma radiation, a large number of odd‐nitrogen clusters were observed, typically Co3N2m‐1+ (m=1–5) and Co4N2m‐1+ (m=1–6) series, showing N≡N bond cleavage in the mild plasma atmosphere. Interestingly, the Co3N7+, Co4N9+, and Co5N9+ clusters exhibit prominent mass abundances. First‐principles calculation results elucidate the stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…The above conclusion is consistent with previous gas-phase studies of MO + catalyzing CH 4 to CH 3 OH that M = Ni affords the best reactivity and selectivity among M = Ni, Pd, and Pt. This inspiring agreement indicates that gas-phase studies on simple molecules/ions are powerful to predict the catalytic behavior of heterogeneous catalysts that bear the same functional units. …”
Section: Resultssupporting
confidence: 88%
“…The above conclusion is consistent with previous gas-phase studies of MO + catalyzing CH 4 to CH 3 OH that M = Ni affords the best reactivity and selectivity among M = Ni, Pd, and Pt. This inspiring agreement indicates that gas-phase studies on simple molecules/ions are powerful to predict the catalytic behavior of heterogeneous catalysts that bear the same functional units. …”
Section: Resultssupporting
confidence: 88%
“…It was found that Co 4 + possesses a relative higher reactivity to form a highly stable complex Co 4 N 9 + which has a Co 4 N core coordinated with four N 2 ligand molecules (Figure b). The superatomic frontier orbital features of Co 4 N 9 + show a swallow-kite structure with superatomic states (1S 2 1P 3 ||1D 0 ) mimicking an arsenic atom (4s 2 4p 3 ||4d 0 ) . These studies not only embody the previously proposed concept of special and general superatoms but also enlighten the rational design of magnetic materials and spin catalysts.…”
supporting
confidence: 63%
“…The superatomic frontier orbital features of Co 4 N 9 + show a swallow-kite structure with superatomic states (1S 2 1P 3 ||1D 0 ) mimicking an arsenic atom (4s 2 4p 3 ||4d 0 ). 28 These studies not only embody the previously proposed concept of special and general superatoms 5 but also enlighten the rational design of magnetic materials and spin catalysts.…”
mentioning
confidence: 99%